2010
DOI: 10.1167/iovs.09-3630
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Arteriolar Vascular Reactivity in Untreated and Progressive Primary Open-Angle Glaucoma

Abstract: Purpose. To determine (1) the magnitude of retinal arteriolar vascular reactivity to normoxic hypercapnia in patients with untreated primary open-angle glaucoma (uPOAG) or progressive (p)POAG and in control subjects and (2) the effect of treatment with 2% dorzolamide on retinal vascular reactivity in uPOAG. Methods. The sample comprised 11 patients with uPOAG (after undergoing treatment, they became treated (t)POAG), 17 patients with pPOAG (i.e., manifesting optic disc hemorrhage), and 17 age-similar control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
(81 reference statements)
1
23
0
1
Order By: Relevance
“…We cannot rule out, however, that other topical agents may also improve retinal vascular autoregulaton. Venkataraman et al 48 have reported an improvement in retinal vascular reactivity to hypercapnia after dorzolamide treatment in patients with POAG. It is our intention is to conduct a prospective study of the effect of brimonidine as well as other topical agents on retinal vascular autoregulation in POAG patients.…”
Section: Discussionmentioning
confidence: 98%
“…We cannot rule out, however, that other topical agents may also improve retinal vascular autoregulaton. Venkataraman et al 48 have reported an improvement in retinal vascular reactivity to hypercapnia after dorzolamide treatment in patients with POAG. It is our intention is to conduct a prospective study of the effect of brimonidine as well as other topical agents on retinal vascular autoregulation in POAG patients.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, patients with glaucoma have faulty autoregulation in response to the lowering of IOP [111]. A study looking at ONH vascular reactivity to normoxic hypercapnia showed that patients with untreated POAG had reduced vascular Review reactivity to healthy controls, thus supporting the concept of vascular dysregulation in glaucoma [112].…”
Section: Onh Blood Flow Alterationsmentioning
confidence: 99%
“…Sines et al [27] berichteten über einen Anstieg der EDV der A. centralis retinae unter Hyperkapnie bei Patienten mit POWG, während die Blutfließgeschwindigkeiten der A. ophthalmica sogar sanken. Venkataraman et al [28] fanden hingegen eine verminderte Antwort der retinalen Gefäße und der Perfusion des Sehnervs mithilfe der Laserdoppler-Flowmetrie bei Patienten mit unbehandeltem und fortschreitendem POWG unter Hyperkapnie. Dies wurde analog zu den hier vorgestellten Ergebnissen als verminderte vaskuläre Reaktivität dieser Patienten interpretiert.…”
Section: Diskussionunclassified